Aku Mengunggah Maka Aku Ada (Kajian Fenomenologis terhadap Autentisitas Identitas Pengguna Facebook) - Harista Hidayah Syaifuddin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
This research shows that the identity of Facebook users displayed in their account is an authentic identity. Authenticity assessment is based on uploading Facebook users that have a match between online and offline conditions. Humans who have the ability to create space actually produce Facebook as a place to spread in the cyber world. This study differs from theoretical findings that emphasize identity originality in cyber space. Identity originality is an assumption that negates the progression of the human figure. This research uses a phenomenological approach in an effort to enable the author to appreciate the Facebook user experience with uploads in his account. The analytical method used is Interpretative Phenomenological Analysis. The data source used is the display of Facebook user accounts which are classified as digital native, namely the millennial generation which has an anchored relationship with the author.